REPUTASI PERUSAHAAN DALAM CARA PANDANG ONTOLOGI - V Mardi Widyadmono; Mugi Harsono (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Corporate reputation is a business buzzword that attracts the scholars and practisioners attention in the last decade. This paper discusses dan provides argumentation on the popularity of corporate reputatation by reviewing the publication of corporate reputation theme at JSTOR, highlights the dynamic aspect of corporate reputation through quoting the Forbes rank on corporate reputation during 2016-2018 and finally, I conclude based on ontology objective and subjective perspective that perception on corporate reputation is not aggregation of all stakeholder. The aggregation of perception on corporate reputation might be performed for a certain corporate stakeholder. This paper contributes on helping researchers in preparing corporate reputation measurement for more comprehensive research on corporate reputation.